Objectives for the use of raw materials and component composition for the production of low-lactose ice cream from goat milk - M. A. Gasheva; T. P. Arseneva; S. Yu. Fadina (Новые технологии)
A huge number of people all over the world suffer from lactose intolerance. The second problem is an allergy to cow milk protein. People with lactose intolerance, as well as those who suffer from cow milk allergies, are forced to significantly limit their choice of ice cream or give it up completely. The article describes a solution to the problem of eating ice cream by children and adults suffering from lactose intolerance and an allergy to cow milk protein, and presents ways to overcome it.The goal of the research. Objectives for the use of raw materials and component composition for the production of low-lactose ice cream from goat milk. During the research, the quality indicators of the selected raw materials have been studied, the characteristics of the main ingredients for the production of low-lactose ice cream have been substantiated and given. Goat milk, in terms of its quality indicators, is most suitable for the production of ice cream, because it contains more protein, fat, solids, less lactose and does not cause allergies, and therefore it has been chosen as the main raw material for the production of ice cream. A theoretical and practical analysis of the chemical composition and properties of goat milk has been carried out, and compared with cow. To reduce the lactose content, a dual method of lactose hydrolysis has been chosen - the use of probiotic starter cultures and the lactase enzyme. In the process of combined hydrolysis at a temperature of 37-39⁰ C for 4-6 hours, a reduction in lactose content of less than 0.9% is achieved, while the concentration of cells of probiotic microorganisms in active form reaches 108 CFU/cm3. It is proposed to use the “Lactomix KM” stabilization system, which is usually used in the production of fermented milk products.